Factors Affecting the Nutritional Status of Toddlers Aged 24-59 Months at the Kertorejo Village Posyandu, Ngoro Subdistrict, Jombang Regency) - Septyaningrum, Rizkyah Wulan; Mudawaroh, Mudawaroh (Formosa Journal of Applied Sciences, 2024)
It is important for parents to know their baby's nutritional status. Poor nutrition inhibits the physical and mental development of early childhood. The main objective of this study was to determine the nutritional status of under-fives at the Posyandu in Kertorejo Village, Ngoro Sub-district, Jombang Regency and the factors that influence it. This study used a cross-sectional research strategy based on observational-analytical principles. A total of 34 newborns were involved in the study. A total of 26 young children were selected as samples using a random sampling procedure. Statistical tests used the Spearman rank test. There was no correlation between maternal knowledge and child nutritional health in the study of children aged 24-59 months in Patuk Hamlet, Kertorejo Village, Jombang Regency (p value 0.524, greater than 0.05).